2021
DOI: 10.1111/joop.12346
|View full text |Cite
|
Sign up to set email alerts
|

A mindfulness intervention promoting work–life balance: How segmentation preference affects changes in detachment, well‐being, and work–life balance

Abstract: This study evaluates a three-week online self-training intervention teaching mindfulness as a cognitive-emotional segmentation strategy. Daily effects on psychological detachment, affective well-being, psychological and strain-based work-family conflict, and satisfaction with work-life balance were assessed, with a particular focus on whether segmentation preferences moderate training responsiveness. A randomized wait-list control group design was used for administering daily questionnaires to 190 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 83 publications
7
58
0
Order By: Relevance
“…We do note that the wording of the segmentation preference scale [13] assesses more of an ability than a preference to separate life spheres and should thus be viewed as a resource rather than a necessity. People lacking this resource, i.e., people low in segmentation preference, can be helped, as these have been shown to profit particularly from a mindfulness intervention targeted at increasing detachment [25]. That childcare duties did not affect need satisfaction or daily work and well-being came as a surprise to us, given that other studies have found parents working from home to be under particular pressure during the pandemic, with mothers often shouldering the greater part of the additional care work [26][27][28].…”
Section: Background Variables: Avenues For Interventionsmentioning
confidence: 99%
“…We do note that the wording of the segmentation preference scale [13] assesses more of an ability than a preference to separate life spheres and should thus be viewed as a resource rather than a necessity. People lacking this resource, i.e., people low in segmentation preference, can be helped, as these have been shown to profit particularly from a mindfulness intervention targeted at increasing detachment [25]. That childcare duties did not affect need satisfaction or daily work and well-being came as a surprise to us, given that other studies have found parents working from home to be under particular pressure during the pandemic, with mothers often shouldering the greater part of the additional care work [26][27][28].…”
Section: Background Variables: Avenues For Interventionsmentioning
confidence: 99%
“…Building on our finding that WTC has a positive effect on IHWI, organizations should train employees on additional boundary management strategies, especially those preventing rumination processes. Michel et al [ 57 ] and Althammer et al [ 58 ] have shown that the use of mindfulness as a cognitive–emotional segmentation strategy is beneficial in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than reducing distress, acceptance aims to increase an individual’s flexibility in responding to their experiences (Hayes et al, 2012). Organizational psychology researchers reported that mindfulness, which is acquired through the acceptance process (Hayes et al, 2012), can help individuals to psychologically detach from work, focus on their present role without distracting thoughts and emotions, and manage the boundaries between the work and family domains, resulting in decreased WFC (Althammer et al, 2021; Kiburz et al, 2017; Michel et al, 2014; Slutsky et al, 2019). These features of mindfulness can also enhance individuals’ engagement in their present role, resulting in positive evaluation of their ability to balance multiple roles, consequently increasing WFE (Allen & Kiburz, 2012; Althammer et al, 2021; Michel et al, 2014).…”
Section: Work–caregiving Interfacementioning
confidence: 99%